OPTIMIZATION OF INVENTORIES AT THE MODERN ENTERPRISE - KHOMENKO, Lyudmila; VODOLAZSKA, Oleksandra; ONYSHCHENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
A necessary condition for improving the efficiency of working capital management in domestic enterprises is a rational justification of the level of costs for their management. At the present stage of economic development, improving the efficiency of inventory management is achieved through the widespread introduction of the logistics concept.The peculiarity of the acquisition of inventory in various ways such as the Tender Committee and the use of automated electronic systems is highlighted. The general indicators characterizing the work of the supply department at the object of research are given, the estimation of the company's commodity flow management is given. Commodity flows within the operating activities of the enterprise are compared and characterized.In order to substantiate management decisions regarding the rationalization of financial investments of current assets, the procurement manager organizes the process of logistics and controls the timeliness of delivery for assessments of compliance with the order and compliance with other contractual terms. It is proposed to include in the organizational structure of the enterprise the Department of Logistics and Procurement, which is subordinated to the announcer for operational activities. The sequence of the current assessment of the supplier is taken into account, taking into account the main parameters that ensure the supply of quality and safe products while calculating the risk of cooperation with the supplier.An approach to strategy development to avoid risks and a mechanism for strategy to restore the supply chain during pandemics and emergencies are proposed. As a result of the research, the ways of improving the management system of commodity flows and their optimization to ensure the normal rhythm of the production process are proposed.
Keywords: working capital; material flows; confectionery; costs; consumers